If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(r + -1) = 3(r + -4) + 6 Reorder the terms: 6(-1 + r) = 3(r + -4) + 6 (-1 * 6 + r * 6) = 3(r + -4) + 6 (-6 + 6r) = 3(r + -4) + 6 Reorder the terms: -6 + 6r = 3(-4 + r) + 6 -6 + 6r = (-4 * 3 + r * 3) + 6 -6 + 6r = (-12 + 3r) + 6 Reorder the terms: -6 + 6r = -12 + 6 + 3r Combine like terms: -12 + 6 = -6 -6 + 6r = -6 + 3r Add '6' to each side of the equation. -6 + 6 + 6r = -6 + 6 + 3r Combine like terms: -6 + 6 = 0 0 + 6r = -6 + 6 + 3r 6r = -6 + 6 + 3r Combine like terms: -6 + 6 = 0 6r = 0 + 3r 6r = 3r Solving 6r = 3r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-3r' to each side of the equation. 6r + -3r = 3r + -3r Combine like terms: 6r + -3r = 3r 3r = 3r + -3r Combine like terms: 3r + -3r = 0 3r = 0 Divide each side by '3'. r = 0 Simplifying r = 0
| 2/3h-5=h+7 | | 14-(6-3x)=3x | | 109=-2(8a-2)+a | | 6(x-7)-7(x-6)=x+6-(x+2) | | 100+0.05m=80+0.70m | | 3(-6x-4)=-120 | | ab-c=d | | 2x-1x+7=x+2 | | Y=45+75X | | 4x+3z=0 | | -7=w | | 4x^2=57x+112 | | -2.2+3= | | 12-3(7+X)=9 | | -1-1=0 | | 51=12x-1+3x+7 | | 21x^2+x=0 | | 4x-0.05(4x)=105.00 | | -X-7=-4x-28 | | 27(.5)+x+100(.1)+x(.25)=180 | | k+23=15 | | 2x+5-4= | | -4(1-1)=11b+7b | | 4x+.05(4x)=105.00 | | -7x-3(5x+18)=144 | | 194=6(4r+7)+8 | | 5x-10=-2x-24 | | 4-(9x+4x)=2(4-4x)+7 | | -8y+30=2u | | 69(2p)=84-4p | | .68=x+x^2 | | -2a+-10+a=-23 |